The importance of engineering mathematics - Mohd. Yassin, Airil Yasreen; Saidina Amin, Norsarahaida (2009)
Engineers are problem solvers whose decisions are constrained by cost and time. Their ideal would be the simultaneous prevalence of the cheapest, the quickest and the safest' decisions'. However, since such an attainment is impossible, what is left is the endeavor for balance between accuracy, efficiency, sufficiency and safety. But, such a diversity, far from being liberating, astringes the engineers to the state of versatility -an engineer should be versatile enough to 'satisfy the various conditions' and this demands ingenuity. Mathematics on the other hand, is the language used in the understanding and deliverance of scientific notions describing the physics of the problems. As far as the appearance of the mathematical terms is concerned, one could not distinguish between physical problems until the specification of certain parameters. In other words, the 'same' mathematical expression would be representative of various equivalent physical problems and the understanding of the derivation and the solution of one typical mathematical statement would allow for the subsequent understanding of the other equivalent problems. Such generality and interconnection between subjects which can only be made possible by the marriage between mathematics and engineering knowledge is what is highly valued nowadays, especially in the advancement of computer technology and that is what this paper is about to venture.